Influência do treinamento motor com biofeedback eletromiográfico na reabilitação da espasticidade após ave e a caracterização da atividade cortical correlata - Vieira, Débora (2016)
Spasticity is observed in most patients after cerebrovascular accident (CVA), and exerts influence in the presence of disabilities, affecting motor function. For neurorehabilitation strategies, electromyographic biofeedback (EMG) has been used with acceptance in the medical community for adjustments in the sensory-motor skills as a motor retraining, reducing spasticity and/or relaxation training. The intervention still presents limited evidence regarding their effectiveness in rehabilitation, especially as the interference of cortical activity and the reduction of spastic signs that provides negative characteristics in movement execution. The aim of this study was to analyze the workout possible interference with EMG biofeedback on the motor control awareness in spastic member in the characterization of the activity of low-frequency bands in different cortical regions targeted by the training technique. Sixteen volunteers affected by ischemic stroke were selected and divided into two groups (n = 8). Experimental group (EG) underwent biofeedback training associated with physical therapy and control group (CG) only conventional physiotherapy. The assessment of the degree of spasticity by reflex threshold of the tonic stretch (TSRT) and Modified Ashworth Scale (MAS) was performed before and three weeks after the end of treatment with the technique. The subjects underwent biofeedback for 6 weeks, with two sessions weekly. The same time for physiotherapy treatment was standardized to the GC. The results show variation of the average percent improvement in the degree of spasticity measured at TRST, 38,59% (sd=13,03%) in GE compared to 18,58% (sd=11,90%) of GC. This variation showed a significant difference (p=0.020; t=2,776; p<5%) between groups (control and experimental), and the significant difference of TRST before and after training in EG (p = 0.003; t=5,338; p <5%) when compared to the CG (p=0.015; t=0,015; p<5%). The semi-quantitative measure of the MAS before and after the end of the sessions presented variations only in GE. Regarding the cortical activity, there were band activities differences when 3rd and 12th sessions were compared for each subject of GE. This difference was found primarily in the frontal, central (vertex), parietal and occipital lobe in both hemispheres (contralateral and ipsilateral to the lesion) in both the cognitive motor planning phase and in the movement execution. It was observed the predominance of activity difference for the delta band, alpha and beta in different subjects distributed diffusely over the EEG recording channels. The different activity of the bands was due to the increase and/or decrease the spectral energy between sessions, x noticed only in some GE volunteers. It was also pointed out distinct activity in secondary motor areas. Evaluations mainly from TSRT show that training with EMG biofeedback was effective in reducing the degree of spasticity. The difference in cortical activity of the frequency bands between sessions suggested that biofeedback modulates cognition through the effort and attention required by the task of movement attempt in the affected limb. Besides that, the spectral energy difference between the sessions depends on the tuning and task complexity driven by biofeedback signals, helping motor learning.